Differentiated Instruction: Challenges and Opportunities in EFL Classroom - Mardhatillah Mardhatillah; Suharyadi Suharyadi (Yayasan Visi Intan Permata, 2023)
The issue of Differentiated Instruction (DI) has recently attracted the attention of scholars and practitioners because of its immense significance and many opportunities to enhance student learning. In this regard, the current study aims to contribute a small summary of DI in the context of EFL to provide context and illustrate the need to implement DI in the classroom to ensure that students learn languages successfully. Since differentiated instruction puts students at the center of teaching and learning, encourages equality and academic achievement, and acknowledges student diversity, it encourages teachers to be aware of individual needs, interests, skills, English proficiency levels, and students’ preferred learning strategies. Although some challenges may occur such as time-consuming and pressure on teachers in implementing DI, this approach has advantages that can affect students' learning processes, future learning attitudes, and future success. So, the learning process provides many opportunities when the teacher is committed to differentiated instruction.